PENERAPAN E-LEARNING PADA SMKN 1 BANDAR LAMPUNG BERBASIS WEB - Yuli Syafitri; Didi Susianto; Reni Astika; Ade Irfandi (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2021)
ABSTRACT E-learning as a learning media in education that provides a very important role and a great function for the education world which has been charged with many shortcomings and weaknesses of education such as the limitations of space and time in the teaching and learning process prioritizing the efficiency of learning in order to get full teaching even though not must be face to face can also be accessed anywhere, anytime, in accordance with the assignments given by the teacher is usually scheduled with a specified deadline. Implementation of E-Learning in SMKN 1 Bandar Lampung Web Based, using Agile Extream Programming system development methods and implemented with Usecase Diagrams, Activity Diagrams, Class Diagrams and using Adobe applications and MySQL Database, as a database designed to be better. The results of this study are a web-based application that is used as E-Learning at SMKN 1 Bandar Lampung which is applied to facilitate student access when they want to get material without having to be constrained by distance and time. And information technology innovations carried out are able to provide information that is response time for system users Keywords: Web; E-learning, agile, extream programming ABSTRAK E-learning sebagai media pembelajaran dalam pendidikan yang memberikan peran sangat penting dan fungsi yang besar bagi dunia pendidikan yang selama ini dibebankan dengan banyaknya kekurangan dan kelemahan pendidikan seperti keterbatasan ruang dan waktu dalam proses belajar mengajar mengedepankan keefisienan dalam belajar agar mendapat pengajaran yang penuh meski tidak harus bertatap muka juga bisa di akses di mana saja, kapan saja, sesuai dengan tugas yang di berikan pengajar biasanya terjadwal dengan batas waktu yang di tentukan. Penerapan E-Learning Pada SMKN 1 Bandar Lampung Berbasis Web, menggunakan metode pengembangan sistem Agile Extream Programming dan diimplementasikan dengan Usecase Diagram, Activity Diagram, Class Diagram dan menggunakan aplikasi Adobe serta Basis Data MySQL, sebagai database yang dirancang menjadi lebih baik. Hasil penelitian ini adaah sebuah aplikasi berbasis web yang digunakan sebagai E-Learning Pada SMKN 1 Bandar Lampung yang diterapkan untuk mempermudah akses siswa ketika ingin mendapatkan materi tanpa harus terkendala oleh jarak dan waktu. Serta inovasi teknologi informasi yang dilakukan mampu memberikan informasi yang bersifat respons time bagi para pengguna sistem. Kata Kunci: Web; E-learning, agile, extream programming